Implementasi Realitas Virtual dalam Pembelajaran Biologi: Tinjauan Literatur Sistematis - Iin Murtini; Imas Cintamulya (Universitas Negeri Jakarta, 2026)
This study aims to investigate how virtual laboratories, cloud-based laboratory platforms, interactive molecular modelling, and serious educational games influence student engagement, conceptual understanding, and motivation. A systematic literature review was conducted on Scopus-indexed studies reporting empirical evaluations or pedagogical implementations of immersive technologies. Eligible studies were screened, coded, and analyzed thematically, emphasizing learning outcomes, instructional scaffolding, user interface design, scalability, and assessment practices. The review found that immersive technologies integrated with inquiry-based pedagogy consistently enhance student engagement and motivation, producing measurable short-term gains in conceptual understanding when supported by explicit scaffolding, timely feedback, and active instructor facilitation. Virtual and cloud-based laboratories expand access to authentic experimental experiences and enable scalable delivery through real-time data integration, while interactive molecular modeling strengthens spatial reasoning and procedural competence. Furthermore, serious educational games effectively promote conceptual transfer when their mechanics are explicitly aligned with instructional objectives.